Torsion of a wandering spleen in an adolescent with Gaucher disease - Güngör, Şükrü; Öztürk, Mehmet; Varol, Fatma İlknur and Sığırcı, Ahmet and Selimoğlu, Mukadder Ayşe (Turkish Journal of Gastroenterology, 2017)
Abstract A wandering spleen is a rare condition characterized by the malposition of the spleen due to laxity or absence of its supporting ligaments. Although Gaucher disease generally presents with massive splenomegaly, which one of the predisposing causes of a wandering spleen, literature shows only one report of a wandering spleen in a child with Gaucher disease. In this case presentation, a 13-year-oldadolescent with Gaucher disease on enzyme replacement treatment was presented, who was detected having an abdominal mass on a routine visit and diagnosed with partial torsion of a wandering spleen associated with left lobe hypoplasia of the liver. Cite this article as: Güngör Ş, Öztürk M, Varol Fİ, Sığırcı A, Selimoğlu MA. Torsion of a wandering spleen in an adolescent with Gaucher disease. Turk J Gastroenterol 2017; 28: 303-6.